Violence, Extremism and Transformation (EBL-Schweitzer, 2010)
Hauptbeschreibung Based on the results of the Bertelsmann Transformation Index 2006 (BTI), this study challenges widespread assumptions and stereotypes about the nature of political violence. It reminds us that religious extremism, while on the rise, accounts for only a small fracture of armed conflict in the world. Moreover, Western countries' preoccupation with transnational terrorism is misleading, as most political violence has been and remains local in its origin and its area of activity. Study results call for a factual and more differentiated assessment of the threats posed by militant